Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan, dan Opini Audit terhadap Ketepatan Waktu Pelaporan Keuangan - Salsabilah Syahfana Amin; Wahyumi Ekawanti (Akuntansi, 2024)
This study aims to determine the influence of Profitability, Liquidity, company size, and audit opinion on the timeliness of financial reporting. The sample selection technique in this study uses purposive sampling and was obtained from 38 Makanan dan Minuman companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The data analysis used in this study is logistic regression analysis using SPSS version 26 software. Based on the results of the study, it can be concluded that profitability has an effect on the timeliness of financial reporting, while company size, and audit opinions have no effect on the timeliness of financial reporting.